1973
DOI: 10.1029/ja078i031p07205
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropies in relativistic cosmic rays from the invisible disk of the Sun

Abstract: The most recent (September 1–2, 1971) of the rare ground level events signaling the arrival at the earth of relativistic solar cosmic rays arising from a flare on the sun's invisible hemisphere displayed marked anisotropy for several hours. Application of newly developed analytical procedures has made it possible to study in detail the evolution of the anisotropic pitch angle distribution. Throughout the anisotropic phase the solar particle flux is proportional to the cosine of the angle between the weighted m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1974
1974
1995
1995

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…McCracken [1962b] has demonstrated that the flux distribution in space is symmetric with respect to an axis which is coincident with the nominal garden hose field line. Several authors have reported that this symmetry in the flux distribution holds for all types of events including those for which the parent solar flares are located on the invisible disk of the sun [Lockwood, 1968; Mathews and Wilson, 1970;Duggal et al, 1971;Maurer et al, 1973;Duggal and Pomerantz, 1973a]. In view of this important result the attempt in recent years has been to determine the exact nature of the angular dependence of the flux with respect to the garden hose field lines [Duggal, 1975].…”
Section: Anisotropy In the Flux Of Solar Cosmic Raysmentioning
confidence: 99%
“…McCracken [1962b] has demonstrated that the flux distribution in space is symmetric with respect to an axis which is coincident with the nominal garden hose field line. Several authors have reported that this symmetry in the flux distribution holds for all types of events including those for which the parent solar flares are located on the invisible disk of the sun [Lockwood, 1968; Mathews and Wilson, 1970;Duggal et al, 1971;Maurer et al, 1973;Duggal and Pomerantz, 1973a]. In view of this important result the attempt in recent years has been to determine the exact nature of the angular dependence of the flux with respect to the garden hose field lines [Duggal, 1975].…”
Section: Anisotropy In the Flux Of Solar Cosmic Raysmentioning
confidence: 99%
“…The maximum intensity was reached 2-3 hours after the onset, and the duration of the GLE was about 8 hours. Analysis of data from several high-latitude neutron monitors by the method outlined by Duggal and Pomerantz [1973] indicates that the pitch For the GLE of August 4, 1972, this procedure leads to the conclusion that t, • 1200 UT. Thus it appears that the acceleration of relativistic particles occurred 2 hours after the termination of the optical activity of the 313 solar flare (Table 1).…”
Section: Stations May Reflect Variations In Asymptotic Directions Camentioning
confidence: 99%